Characteristics of substance use disorder treatment patients using medical cannabis for pain. (March 2015) - Ashrafioun, Lisham; Bohnert, Kipling M.; Jannausch, Mary; Ilgen, Mark A.
Abstract: Background: This study was designed to assess the prevalence and correlates of self-reported medical cannabis use for pain in a substance use disorder (SUD) treatment program. Method: Participants ( n = 433) aged 18 years and older were recruited from February 2012 to July 2014 at a large residential SUD treatment program. They completed a battery of questionnaires to assess demographics, usual pain level in the past three months (using the 11-point Numeric Rating Scale for pain), depression (using the Beck Depression Inventory), previous types of pain treatments, and lifetime and past-year use of substances (using the Addiction Severity Index). Using both adjusted and unadjusted logistic regression models, we compared those who reported medical cannabis use for pain with those who did not report it. Results: Overall, 15% of the sample ( n = 63) reported using medical cannabis for pain in the past year. After adjusting for age, medical cannabis use for pain was significantly associated with past-year use of alcohol, cocaine, heroin, other opioids, and sedatives, but was not associated with usual pain level or depression. It was also associated with past year treatment of pain using prescription pain relievers without prescriptions. Conclusions: These results indicate that medical cannabis use for pain is relatively common and is associated with more extensive substance use among SUD patients. Future work is needed to develop and evaluate strategies to assess and treat individuals who report medical cannabis for pain in SUD treatment settings. Highlights: Study was designed to assess correlates of medical cannabis use for pain. 15% of sample from substance use disorder treatment reported medical cannabis use. Medical marijuana use for pain was associated with greater past-year substance use. Research is needed to inform providers about medical cannabis use in drug treatment.